Asbestos Contamination in Talc-Based Cosmetics: An Invisible Cancer Risk. (November 2020) - Stoiber, Tasha; Fitzgerald, Sean; Leiba, Nneka S
The lack of regulation and adequate testing of talc-containing personal care products in the U.S. has resulted in the contamination of cosmetics with asbestos. As such, the true exposure of consumers to asbestos is poorly characterized and likely underestimated. In this study, transmission electron microscopy analysis revealed that 3 of 21 powder-based cosmetic products tested were contaminated with amphibole asbestos. One of these contaminated products is expressly marketed for use by children. The presence of asbestos found in products demonstrates the urgency to revise cosmetics policy. Further, talc-based cosmetics may be an overlooked and difficult to characterize source of exposure to asbestos, a known carcinogen.